Medical Diagnosis System for Glaucoma Diseases Detection Based On Retinal Images Using Data Mining Techniques - Pary, G; Aramudhan, M; Thirumoorthy, N (International Journal of Computer Sciences and Engineering, 2018)
The main objective of this research paper is to present an analysis of different types of data mining techniques for the detection of glaucoma. It is one of the serious eye diseases. The Glaucoma affects the optic nerve in retina. In which the retinal ganglion cells are in dead condition and this leads to permanent loss of vision. So the early detection of glaucoma is needed to prevent the patients from diseases. The Manual analysis of retinal images is fairly time-consuming and accuracy depends on the expertise of the professionals. By the proposed Medical diagnosis system mass screening is possible to help the doctor for take proper treatment.